The Impact of Superheated Liquids in the Direct Search for Astroparticle Dark Matter - M. Felizardo (Current Research Progress in Physical Science Vol. 6, 2024)
Aims: The emergence of the superheated liquid technique in the direct search for astroparticle dark matter has had a significant impact on the international dark matter search effort. It differs from other techniques in recording the sound associated with the transition of a metastable liquid to its gas phase stimulated by incident particle energy loss. Place and Duration of Study: Department of Nuclear Engineering and Sciences, Lisbon, Portugal between June 2024 and November 2024. Methodology: Among its advantages is a tuneable 10-10 level insensitivity to the majority of traditional detector backgrounds which plague more conventional dark matter search detectors, and discrimination of the remainder. The insensitivity is not trivial, translating to a reduced data record, and simplified, more efficient analyses of the results. Results: The straightforwardness of the detectors, their instrumentation and data analysis, and their capacity for target variations have provided at a minimum a relatively inexpensive and competitive search approach. Conclusion: A description of the prominent dark matter search aspects common to the four superheated liquid efforts (SIMPLE, COUPP, PICASSO, PICO), with some comparison made with those of the other more traditional techniques in use.